An integrated framework for safety, quality and risk management: an information and incident management system based on a universal patient safety classification. (1st December 2006) - Runciman, W B; Williamson, J A H; Deakin, A; Benveniste, K A; Bannon, K; Hibbert, P D
Abstract : More needs to be done to improve safety and quality and to manage risks in health care. Existing processes are fragmented and there is no single comprehensive source of information about what goes wrong. An integrated framework for the management of safety, quality and risk is needed, with an information and incident management system based on a universal patient safety classification. The World Alliance for Patient Safety provides a platform for the development of a coherent approach; 43 desirable attributes for such an approach are discussed. An example of an incident management and information system serving a patient safety classification is presented, with a brief account of how and where it is currently used. Any such system is valueless unless it improves safety and quality. Quadruple-loop learning (personal, local, national and international) is proposed with examples of how an exemplar system has been successfully used at the various levels. There is currently an opportunity to "get it right" by international cooperation via the World Health Organization to develop an integrated framework incorporating systems that can accommodate information from all sources, manage and monitor things that go wrong, and allow the worldwide sharing of information and the dissemination of tools for the implementation of strategies which have been shown to work.